Exploring The Landscape Of Food Safety Knowledge And Practice Among Malaysian Secondary School Students - Shalinawati Ramli; Shahlan Surat; Nurul Azmawati Mohamed; Mohd Dzulkhairi Mohd Rani; Masyita Mamot; Azizah Mat Hussin; Choong Siew Shean (INTERNATIONAL JOURNAL OF ACADEMIC RESEARCH IN P, 2024)
Indexed by ERA